gdSir2.1 and gdSir2.3 are involved in albendazole resistance in Giardia duodenalis via regulation of the oxidative stress response - Adrián Chávez-Cano; Scott C. Dawson; M. Guadalupe Ortega-Pierres (International Journal for Parasitology: Drugs and Drug Resistance)
Albendazole resistance in Giardia duodenalis includes a complex and multifactorial challenge that potentially involves non-reported pathways such as the participation of metabolic regulators. In this context, sirtuins, known as metabolic sensors in various cellular processes, have emerged as promising candidates for novel anti-parasitic treatments. To investigate their role in albendazole (ABZ) resistance, initially we analyzed the expression of sirtuins in three Giardia strains resistant to 8 μM, 1.5 μM and 250 μM of ABZ that were obtained in our laboratory. Additionally, we used a CRISPRi-based knockdownstrategy to repress several sirtuins in Giardia and analyzed the effect of sirtuins on ABZ resistance. Our findings demonstrated a significant upregulation of sirtuins gdSir2.1, gdSir2.2 and gdSir2.3 in the three distinct albendazole-resistant lines. Knockdown of gdSir2.1 and gdSir2.3 resulted in heightened parasite susceptibility to both albendazole and hydrogen peroxide. Further, our study suggested that sirtuins contribute to the regulation of reactive oxygen species (ROS) levels, oxidative DNA damage, and the expression of oxidative stress response (OSR) genes within the parasite. Collectively, our results demonstrated that gdSir2.1 and gdSir2.3 play a significant role in mediating albendazole resistance, primarily through regulating the oxidative stress response.